Identifikasi bakat olahraga di kalangan anak-anak di Malang - Hariadi, Imam; Hanief, Yulingga Nanda; Fadhli, Nurrul Riyad (Universitas Nusantara PGRI Kediri, 2022)
Talent Identification is essential to identify the potential of young athletes to succeed in senior elite sports. This study aimed to identify talent in sports among children in Malang. This research was an observational cross-sectional study involving 356 children (68% boys) who were purposively selected in Malang city based on age criteria (age 11 years old). Several tests and measurements were conducted for talent identification, including anthropometric tests, eye-hand coordination, leg muscle power, arm muscle power, agility, speed, and VO2max. Sports talent identification was conducted based on Norm developed by Narlan and Juniar. The results were matched into a sports talent profile table according to the age and gender of the participants. Results with the sports branch profile norms were matched, if the test results were at least the same or better than the sports study program, then the child was